Electrochemical Nano-Imprinting of Trimetallic Dendritic Surface for Ultrasensitive Detection of Cephalexin in Pharmaceutical Formulations - Rohini Kumari; Pranjal Chandra (MDPI AG, 2023)
Cephalexin (CFX), a first-generation cephalosporin, is used to treat various infectious diseases. Although antibiotics have achieved considerable progress in the eradication of infectious diseases, their incorrect and excessive usage has contributed to various side effects, such as mouth soreness, pregnancy-related pruritus, and gastrointestinal symptoms, including nausea, epigastric discomfort, vomiting, diarrhoea, and haematuria. In addition to this, it also causes antibiotic resistance, one of the most pressing problems in the medical field. The World Health Organization (WHO) claims that cephalosporins are currently the most commonly used drugs for which bacteria have developed resistance. Hence, it is crucial to detect CFX in complex biological matrices in a highly selective and sensitive way. In view of this, a unique trimetallic dendritic nanostructure comprised of cobalt, copper, and gold was electrochemically imprinted on an electrode surface by optimising the electrodeposition variables. The dendritic sensing probe was thoroughly characterised using X-ray photoelectron spectroscopy, scanning electron microscopy, chronoamperometry, electrochemical impedance spectroscopy, and linear sweep voltammetry. The probe displayed superior analytical performance, with a linear dynamic range between 0.05 nM and 105 nM, limit of detection of 0.04 ± 0.01 nM, and response time of 4.5 ± 0.2 s. The dendritic sensing probe displayed minimal response to interfering compounds, such as glucose, acetaminophen, uric acid, aspirin, ascorbic acid, chloramphenicol, and glutamine, which usually occur together in real matrices. In order to check the feasibility of the surface, analysis of a real sample was carried out using the spike and recovery approach in pharmaceutical formulations and milk samples, yielding current recoveries of 93.29-99.77% and 92.66-98.29%, respectively, with RSD < 3.5%. It only took around 30 min to imprint the surface and analyse the CFX molecule, making it a quick and efficient platform for drug analysis in clinical settings.